X-Men: Days of future past - The Rogue cut [videorecording (Blu-Ray)] - Singer, Bryan, 1965-; Jackman, Hugh; McKellen, Ian; Stewart, Patrick, 1940-; Berry, Halle (20th Century Fox Home Ent., 2015)
Extended cut of the blockbuster superhero sequel based on the characters from the Marvel comic strip. With a storyline that alternates between the past and present, the film acts as a direct sequel to three separate films, 'X-Men: The Last Stand' (2006), 'X-Men: First Class' (2011) and 'The Wolverine' (2013). When the survivors of the battle in 'X-Men: The Last Stand', led by Magneto (Ian McKellen), Professor X (Patrick Stewart) and Storm (Halle Berry), discover that total annihilation now awaits humans and mutants alike, they send the ageless Wolverine (Hugh Jackman) back in time to try and change the course of events. In the past, Wolverine must team up with the younger incarnations of the X-Men seen in 'X-Men: First Class', Charles Xavier (James McAvoy), Magneto (Michael Fassbender) and Mystique (Jennifer Lawrence), to avert disaster. Will he succeed? This extended cut features an extra 17 minutes of previously deleted scenes that focus on the character of Rogue, played by Anna Paquin.